2020
DOI: 10.1021/acs.organomet.0c00417
|View full text |Cite
|
Sign up to set email alerts
|

Origins of Batch-to-Batch Variation: Organoindium Reagents from Indium Metal

Abstract: Yields of organoindium reagents synthesized from indium metal were previously reported to be highly dependent on metal batch and supplier due to the presence or absence of anticaking agent. Here, single-particle fluorescence microscopy established that MgO, an additive in some batches nominally for anticaking, significantly increased the physisorption of small-molecule organics onto the surface of the resulting MgO-coated indium metal particles. An inert and relatively nonpolar boron dipyrromethene fluorophore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…The dramatically lower lifetime of 2 compared to 1 is attributed to quenching by the zinc surface. [37,38] The substantially increased lifetime of 4 (τ solution = 4.6 ns) compared to 2 (τ surface � 0.8 ns) is attributed to removal of the organozinc from its proximity to the quenching zinc metal surface; the shorter lifetime of 4 (τ solution = 4.6 ns) compared to 1 (τ solution = 5.5 ns) is attributed to the presence of zinc(II) in molecular 4. [42,43] (See Scheme S3 for the regions of interest used for each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…The dramatically lower lifetime of 2 compared to 1 is attributed to quenching by the zinc surface. [37,38] The substantially increased lifetime of 4 (τ solution = 4.6 ns) compared to 2 (τ surface � 0.8 ns) is attributed to removal of the organozinc from its proximity to the quenching zinc metal surface; the shorter lifetime of 4 (τ solution = 4.6 ns) compared to 1 (τ solution = 5.5 ns) is attributed to the presence of zinc(II) in molecular 4. [42,43] (See Scheme S3 for the regions of interest used for each measurement.…”
Section: Methodsmentioning
confidence: 99%
“…As chemists, we still do not generally know the answers to these questions. Single-particle fluorescent microscopy studies found differences in reactivity behaviors between individual nanoparticles [17,32], zeolite particles [13,53], metallic zinc [4,35], indium [58], particles in powders in addition to the growing polymer aggregates [41,42]. In fascinating recent work, Sambur identified that individual particles displayed different electrochromic dynamics, impacting the durability and speed of tinting of smart windows on the macroscale [22]; on account of the natural spectral changes of these particles, addition of a fluorescent imaging agent was not required for these measurements.…”
Section: Trends In Chemistrymentioning
confidence: 99%
“… The mechanistic causes of these reactivity differences remain, however, poorly understood . Without the ability to understand the cause of variation in different batches of Rieke zinc, , the rational selection of the best preparation by users is not straightforward, and the expansion of this useful chemistry to access new carbon–(pseudo)­halide bond insertion, polymers, and nanomaterials is impeded.…”
Section: Introductionmentioning
confidence: 99%